Desarrollo de la neuro función básica: psicomotricidad, en niños de primero de educación básica en la Unidad Educativa The Oxford Gardens School - Pilaguano Cordones, Kerlin Dayana (2025)
The present research aimed to analyze the development of the basic neuro function psychomotricity in first-grade students of The Oxford Gardens School. The objective was to identify the levels of gross motor skills and visuomotor coordination in to establish strategies that support the psychomotor development process. The direct beneficiaries were the first-grade students of this institution, since the study made it possible to identify their levels of gross motor skills and visuomotor coordination, with the purpose of establishing strategies that would contribute to the psychomotor development process of first-grade students. The research was developed under a quantitative approach, with a non-experimental, basic, and field research design. According to its level, it was classified as descriptive and carried out with a cross-sectional approach applied over a specific period of time. Furthermore, an intentional sample was used, consisting of 12 first-grade students from general basic education, and a psychometric technique was applied using the TEPSI test (Psychomotor Development Test) for children aged 2 to 5 years. The results show that 75% of the students achieved normal development, 17% showed delay, and 8% were at risk. This demonstrates the need to implement playful strategies that strengthen their psychomotor skills.